Tablet Granulasi Basah Asam Mefenamat dengan Pewarna Ekstrak Daging Buah Naga Merah (Hylocereus polyrhizus Britton and Rose) - Siti Elisa; Vriezka Mierza (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Natural dyes have been used for a long time, and are generally considered safer than synthetic dyes, including red anthocyanins, which are produced, among others, by red dragon fruit. Dyes can be used to provide identity to products, making product identification easier, and helping to minimize the possibility of confusion during the production process. The addition of colouring to the tablet also adds aesthetic value. On the market mefenamic acid tablets are white, they have not been found in other colours. Objective: The research was directed to determine whether red dragon fruit flesh extract can be used as a natural colouring in mefenamic acid tablet preparations using the wet granulation method. Method: Red dragon fruit flesh extract was prepared by maceration using 96% ethanol. Results: Tablet formulations were made from formulas 1 to 6 with red dragon fruit extract 9 each; 10; 14.5; 12.5; 16.5; and 18.5%. The best formula for red dragon fruit juice is formula 2, for red dragon fruit flesh extract the best formula is formula 3, 4, 5 and 6. Because it meets the requirements of the Indonesian Pharmacopoeia Edition VI. Conclusion: Red dragon fruit extract and juice can be moulded into tablets, meeting all quality requirements of the Indonesian Pharmacopoeia Edition VI